2007
DOI: 10.1590/s1807-59322007000600014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intertrochanteric Osteotomy on the Proximal Femur of Rabbits: Assessment With Power Doppler Sonography and Scintigraphy

Abstract: 1Doria AS, Cunha FG, Modena M, Rodrigues CJ, Garcez AT, Junior RG, Bolliger Neto R, Melo IB, Buchpiguel C, Molnar LJ, Guarniero R. Effect of intertrochanteric osteotomy on the proximal femur of rabbits: assessment with power doppler sonography and scintigraphy. Clinics. 2007;62(6):741-8. OBJECTIVE:In bone injury, repair results in local increased vascularity and bone marrow remodeling. Characterizing the vascular and metabolic imaging patterns of the proximal femur following an intertrochanteric osteotomy may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0
1

Year Published

2009
2009
2011
2011

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
1
0
1
Order By: Relevance
“…Bone overgrowth is thought to be caused by 2 increased vascularity. Doria et al 25 showed postoperative hypervascularity after femoral 3 osteotomy in rabbits. This report did not deal with postoperative radius hypervascularity.…”
mentioning
confidence: 97%
“…Bone overgrowth is thought to be caused by 2 increased vascularity. Doria et al 25 showed postoperative hypervascularity after femoral 3 osteotomy in rabbits. This report did not deal with postoperative radius hypervascularity.…”
mentioning
confidence: 97%
“…pode auxiliar em casos onde não há clareza no diagnóstico radiográfico. Com relação à regeneração óssea, o trabalho descreveu a facilidade na visualização do calo e salientou a antecipação da identificação com relação ao exame radiográfico, inclusive com relação à consolidação da fratura, sendo esta Power Doppler pode ser utilizado para reconhecer padrão vascular de imagem, porém, esta técnica exige do examinador conhecimento prévio do processo que ocorre durante os fenômenos fisiológicos do processo regenerativo das fraturas(DORIA et al, 2007;RAHIMZADEH et al, 2012). Este método pode detectar temperatura superficial de forma mais objetiva quando comparada ao exame clínico de palpação(HEAD;DYSON, 2001;REDAELLI et al, 2014).…”
unclassified